Relationship Between Individual Factors And Work Factors With Work Stress At The Harbor Mobile Crane Operator (HMC) At PT. Pelabuhan Indonesia (Persero) Sub Regional III East Java - Al-Faris, Muhammad Nadhori Faqih; Wijaya, Satria; Handayani, Dwi; Ayu, Friska (Universitas Nahdlatul Ulama Surabaya, 2022)
The implementation of K3 cannot be separated from the existence of Occupational Diseases and Occupational Accidents. One of the jobs that are at risk of experiencing Occupational Diseases and Occupational Accidents is the Harbor Mobile Crane Operator. One of the diseases caused by work is work stress. The purpose to analyze the relationship between individual factors and work factors on the work stress of Harbor Mobile Crane operators at PT. Pelabuhan Indonesia (Persero) Sub Regional III East Java. The research methodology used is an analytical survey research with a Cross Sectional approach. The primary data was collected by taking the sample through the DASS 21 questionnaire while the secondary data through the company profile provided by the Branch Manager of PT Pelabuhan Indonesia (Persero) Sub Regional III East Java. The research sample was 26 operators which were taken from the entire population. Data analysis used chi-square test for nominal data and Spearman correlation test for ordinal data. The results showed that most of the operators experienced is normal and a small portion experienced heavy work stress. Factors related to operator work stress, namely, age, marital status, education level, work period and shift work. The results of relationship test of marital status showed a relationship with work stress and the others factor is not showing relationship with work stress. The conclusion of the study shows that there is a relationship between individual factors with operator work stress. From the results of the study, companies are advised to give a conselling session to the unmartial operators to reduce work stress operators.